Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1080/09168451.2015.1042832
|View full text |Cite
|
Sign up to set email alerts
|

Development of preparative and analytical methods of the hop bitter acid oxide fraction and chemical properties of its components

Abstract: The bitter acids in hops (Humulus lupulus L.) and beer, such as α-, β-, and iso-α-acids, are known to affect beer quality and display various physiological effects. However, these compounds readily oxidize, and the effect of the oxides on the properties of beer or their potential health benefits are not well understood. In this study, we developed a simple preparative method for the bitter acid oxide fraction derived from hops and designated the constituents as matured hop bitter acids (MHBA). HPLC-PDA-ESI/HRM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 45 publications
1
43
0
Order By: Relevance
“…Finally, MHE was yielded as brown powder (approximately 7.6 kg). HPLC analysis confirmed that the MHE contained 20.5% of MHBA, as previously described (Taniguchi et al, 2015).…”
Section: Preparation Of Test Substancesupporting
confidence: 74%
See 1 more Smart Citation
“…Finally, MHE was yielded as brown powder (approximately 7.6 kg). HPLC analysis confirmed that the MHE contained 20.5% of MHBA, as previously described (Taniguchi et al, 2015).…”
Section: Preparation Of Test Substancesupporting
confidence: 74%
“…In contrast, oxidation of α-and β-acids produces bitter acid oxides, such as matured hop bitter acids (MHBA). All of the structurally elucidated compounds of MHBA possess a common β-tricarbonyl moiety similar to α-, β-, and isoα-acids (Taniguchi et al, 2013(Taniguchi et al, , 2014a(Taniguchi et al, , 2014b(Taniguchi et al, , 2015. We demonstrated that MHBA suppresses diet-induced body fat accumulation in animals (Morimoto-Kobayashi et al, 2015).…”
Section: Introductionmentioning
confidence: 75%
“…Representative IAA compounds include isocohumulone, isohumulone, and isoadhumulone, depending on the particular acyl side chain structure present, and each compound has cis and trans isomers ( Figure 1). Taniguchi et al [16] further determined the concentration of IAAs in commercially available beers and found 16-27 mg/L of IAAs in lager-type Japanese beer and 41-64 mg/L of IAAs in India Pale Ale, which is brewed with a large amount of hops.…”
Section: Characterization Of Iaasmentioning
confidence: 99%
“…According to the allometric scaling to human dose, 0.2-2 mg/kg of IAAs is equivalent to 0.03-0.3 mg/kg (2-20 mg in 70-kg person) in humans. Taniguchi et al [16] reported that 16-27 mg/L of IAAs are contained in regular types of beer, and thus effective dose of IAAs would be found in 0.13-1.3 L of beer.…”
Section: Iaas Enhance Cognitive Function Via Activation Of the Vagus mentioning
confidence: 99%
See 1 more Smart Citation